Bioactive Polysaccharides from Phyllostachys nigra as Prebiotic Agents: Effects on Short-Chain Fatty Acid Production and Host Metabolism - Noah Bennett; Ralph Graves; Mason Garrett; Wayne J. Salonen (International Journal of Clinical and Translational Medicine, 2026)
The gut microbiome functions as a highly distributed, multi-agent metabolic network that transduces dietary inputs into systemic physiological signals, many of which are mediated by short-chain fatty acids (SCFAs). Non-digestible polysaccharides that selectively stimulate beneficial microbial taxa—prebiotics—are increasingly recognized not merely as nutritional supplements but as system-level interventions capable of reconfiguring host-microbial information flow, metabolic pathway allocation, and endocrine feedback loops. This paper examines the prebiotic potential of bioactive polysaccharides derived from the black bamboo species Phyllostachys nigra. Drawing on emerging structural and functional evidence, the analysis explores how the unique monomeric composition, glycosidic linkage patterns, and molecular weight distribution of these polysaccharides shape their fermentation kinetics, SCFA profiles, and subsequent effects on host glycolipid metabolism. Moving beyond reductionist biochemical description, the paper adopts a socio-technical and infrastructural lens to assess the architecture of gut microbial ecosystems under polysaccharide perturbation, the robustness and resilience of SCFA-producing networks, and the fairness implications of prebiotic deployment strategies. Production scalability, bamboo feedstock sustainability, regulatory governance, and integration into public health infrastructures are critically evaluated. The system-level perspective reveals structural trade-offs between personalization and population-wide standardization, between rapid fermentability and distal colonic targeting, and between ecological diversity and therapeutic specificity. By reframing a traditional nutraceutical topic within the discourse of complex systems, governance, and policy, the paper identifies knowledge gaps and proposes a research agenda that foregrounds architectural design principles for microbiome-directed nutrition.